Pengaruh Struktur Modal Terhadap Kinerja Keuangan Bank Komersial Konvensional di Indonesia - Kesuma Dewi Safitri; Ickhsanto Wahyudi (Politeknik Ganesha Medan, 2025)
In the banking world, the chosen capital structure will have a direct impact on the bank's ability to finance operational activities, manage risk, and maintain long-term financial stability. Therefore, this research was conducted to evaluate how far decisions related to capital structure can affect the financial performance of 22 conventional commercial banks on the IDX in 2021-2024, an analysis technique using the Stata 15 program with the Random Effect Model (REM). In this study, a quantitative approach with an explanatory study design was used. The t-test in this research shows that LDR and DTAR show a positive and significant influence on financial performance, while ATER shows a negative and significant influence on financial performance. The CAR and GA did not show a significant influence on financial performance. The results of this study imply that banks need to maintain a balanced capital structure, particularly in managing liquidity and funding ratios, to improve the effectiveness of financial performance.